2022
DOI: 10.7717/peerj.13292
|View full text |Cite
|
Sign up to set email alerts
|

Identification, diversity and domain structure analysis of mucin and mucin-like genes in sea anemone Actinia tenebrosa

Abstract: Background Mucins are part of the glycoprotein family and the main proteinaceous component of mucus. The sea anemone species, Actinia tenebrosa (Phylum Cnidaria) produce large amounts of mucus, which have not been studied in detail. Furthermore, there has only been limited investigation of mucin genes in phylum Cnidaria. Therefore, the aim of current study was to identify and analyse the repertoire mucin genes present in A. tenebrosa and range of other sea anemone species to document their diversity in this gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Supporting this early study, a layer of mucin-secreting glandular cells associated with oocyte development has been also mentioned by Levitan et al (2015) and Moiseeva et al (2017) for N. vectensis. Mucin genes of Actinia tenebrosa Farquhar, 1898 were analyzed by Haridi (2022), suggesting a diverse genetic repertory of this proteinaceous component of mucus, which was considered to be consistent with the conserved domains in the homologous proteins of the vertebrates. Using transcriptomic and proteomic analysis, Takeuchi et al…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Supporting this early study, a layer of mucin-secreting glandular cells associated with oocyte development has been also mentioned by Levitan et al (2015) and Moiseeva et al (2017) for N. vectensis. Mucin genes of Actinia tenebrosa Farquhar, 1898 were analyzed by Haridi (2022), suggesting a diverse genetic repertory of this proteinaceous component of mucus, which was considered to be consistent with the conserved domains in the homologous proteins of the vertebrates. Using transcriptomic and proteomic analysis, Takeuchi et al…”
Section: Introductionmentioning
confidence: 95%
“…(2016) described the process of coral skeletogenesis, identifying transmembrane proteins in the skeletal organic matrix of the scleractinian Acropora digitifera (Dana, 1846). Signal transduction and protective barrier (against bacteria and other infectious microorganisms) are among the main functions described for the mucin layer in vertebrates (Moiseeva et al 2017;Haridi 2022). However, its connection with gametogenesis in Cnidaria has not been fully interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome annotation was conducted using the Trinotate pipeline V3.0 following method detailed as per [13] for details. Gene Ontology (GO) terms were assigned to contigs that received BLAST hits and had functional annotation information.…”
Section: Functional Annotation and Gene Ontologymentioning
confidence: 99%
“…Consequently, mucins are multifunctional proteins and likely undertake multiple roles also in cnidarian species. In previous cnidarian mucins study by [13] a repertoire of mucin genes was identified in A. veratra, but the study did not investigate the mucin expression in this species.…”
Section: Introductionmentioning
confidence: 99%
“…Clusters 17, 22 and 24 co-occur and are likely to be digestive gland cell types (Supplementary Figure 1D). mucosal gland cells (21, 32): Rsp+ cells, cluster 21, were named after the specific ortholog markers of rhamnospondin (LOC130621200, LOC130655212, LOC130622532), a known gland cell marker likely for production of the outer mucosal layer (glycocalyx) 69 . Cluster 32 was identified as gland 4 cells due to the shared low expression of one rhamnospondin ortholog (LOC130622532).…”
Section: Supplementary Note 1: Explanation Of Cluster Naming and Grou...mentioning
confidence: 99%